Upaya Meningkatkan Kesadaran Ibu tentang Pentingnya Posyandu di RW 03 Desa Babakan - Shanti Ariandini; Angelika Putri; Neng Aryani; Dela Amalia; Reffy Septyani (STIKes Ibnu Sina Ajibarang, 2025)
One of the major issues commonly found in Indonesia, particularly within communities, is the problem of unbalanced nutrition. This has contributed to a decrease in the function and performance of Posyandu by approximately 40%. Therefore, community support and equitable health development in every village are essential (Indrasari et al., 2024). This study is an analytical observational research with a cross-sectional design, conducted by four university students in RW 03, Babakan Village, Ciseeng Subdistrict, Bogor Regency, in January 2025. The method used in this community service project is health education, as we believe it to be an effective approach for increasing interest and participation in Posyandu, particularly among mothers with infants and toddlers. The researchers observed that many mothers already understand the importance of Posyandu, especially for the health of their babies and toddlers. However, based on data collected from Posyandu cadres prior to the counseling session, some mothers were still hesitant to bring their children to Posyandu, which hindered its effectiveness. After the counseling session, there was a noticeable improvement—mothers' knowledge increased, and their awareness of the importance of Posyandu was significantly enhanced (Hafifah & Abidin, 2020).